Analysis of Factors Influencing Consumer Purchase Decisions for Coffee Shops in Tomohon City - Bura, Eben C. P.; Mawuntu, Priska Shirty Thelma; Aotama, Reynaldo Christian (Universitas Diponegoro, 2023)
The coffee shop has now become a phenomenon in the community, drinking coffee is now no longer just to eliminate sleepiness, but as part of a lifestyle where the coffee shop is a very popular gathering place. The city of Tomohon is also inseparable from the phenomenon of coffee shops where coffee shops have begun to appear in various locations around the Tomohon city. This study aims to determine the factors that influence consumer purchasing decisions on coffee shops in Tomohon City by conducting a case study at Elmonts Coffee & Roastery Tomohon. The method used in this research is a qualitative case study method. Data collection techniques are carried out by in-depth interviews, observation, and documentation. The data validity technique used is source triangulation and triangulation techniques with data analysis techniques namely Miles and Huberman model analysis techniques. The results showed 6 factors that influenced purchasing decisions at a coffee shop in Tomohon City, namely product, atmosphere, social, promotion, location, and brand.